Cotinine and 6-Hydroxy-L-Nicotine Reverses Memory Deficits and Reduces Oxidative Stress in Aβ25-35-Induced Rat Model of Alzheimer's Disease - Razvan Stefan Boiangiu; Marius Mihasan; Dragos Lucian Gorgan; Bogdan Alexandru Stache; Brindusa Alina Petre; Lucian Hritcu (MDPI AG, 2020)
The nicotinic derivatives, cotinine (COT), and 6-hydroxy-L-nicotine (6HLN), showed promising cognitive-improving effects without exhibiting the nicotine's side-effects. Here, we investigated the impact of COT and 6HLN on memory impairment and the oxidative stress in the Aβ25-35-induced rat model of Alzheimer's disease (AD). COT and 6HLN were chronically administered to Aβ25-35-treated rats, and their memory performances were assessed using in vivo tasks (Y-maze, novel object recognition, and radial arm maze). By using in silico tools, we attempted to associate the behavioral outcomes with the calculated binding potential of these nicotinic compounds in the allosteric sites of α7 and α4β2 subtypes of the nicotinic acetylcholine receptors (nAChRs). The oxidative status and acetylcholinesterase (AChE) activity were determined from the hippocampal tissues. RT-qPCR assessed bdnf, arc, and il-1β mRNA levels. Our data revealed that COT and 6HLN could bind to α7 and α4β2 nAChRs with similar or even higher affinity than nicotine. Consequently, the treatment exhibited a pro-cognitive, antioxidant, and anti-AChE profile in the Aβ25-35-induced rat model of AD. Finally, RT-qPCR analysis revealed that COT and 6HLN positively modulated the bdnf, arc, and il-1β genes expression. Therefore, these nicotinic derivatives that act on the cholinergic system might represent a promising choice to ameliorate AD conditions.